Conversations with strangers : performing the broom & the bricoleur - Doidge, Malcolm (Massey University, 2015)
Within a workshop or studio, Bricolage is a process where the artist-as-bricoleur finds ad hoc collections of items and recombines them in unusual ways. A bricoluer uses simple tools for many tasks. This thesis considers how a contemporary bricoleur might step away from the workshop and into the everyday, taking only a broom as a familiar tool. “Conversations with strangers” performs the bricoleur at five sites, where the broom is a device that collects fragments of memories from conversations recorded there. These conversations form an inventory or collection that is a palimpsest merging human dialogue with a layer of sound from the sites as the broom sweeps. Together with the broom, these fragments are repurposed within a sculptural installation and post-studio performance of the Bricoleur.
Keywords: Doidge, Malcolm; Criticism and interpretation; Brooms and brushes in art; Installations (Art)